Carcinomas of the small intestine in sheep : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University - Simpson, Bruce Henry (Massey University, 1971)
Carcinomas of the small intestine were long considered uncommon neoplasms in all species. Over the last decade there has been a growing awareness that, contrary to this belief, small intestinal carcinomas are common in sheep, at least in New Zealand. Not only is this high incidence of an otherwise rare neoplasm scientifically intriguing, but it is also of potential economic importance both to individual farmers and to meat slaughtering firms. In addition, the possibility of the existence, in the rural environment, of an unrecognised carcinogen to which man also might be susceptible adds to the importance of this disease. These factors stimulated the initiation of the present investigation into the pathology, prevalence, epidemiology and aetiology of this neoplasm, results of which form the basis of this thesis. Included also are reviews of the pertinent literature concerning small intestinal carcinomas of other species, including man, and of neoplasia of sheep in general. The results of preliminary experiments to investigate the effect of known carcinogens on sheep are also reported.
Keywords: Cancer; Sheep diseases; Carcinomas